Synthesis, Crystal Structure, Spectroscopic and Electronic Properties of (E)-Trans-2-(2-(Biphenyl-4-ylmethylene)Hydrazinyl)-4-(3-Methyl-3-Phenylcyclobutyl)Thiazole - Yuksektepe, Cigdem; Caliskan, Nezihe; Yilmaz, Ibrahim; Cukurovali, Alaaddin (Springer/Plenum Publishers, 2010)
A new compound of (C27H25N3S) has been synthesized and characterized by H-1 NMR, C-13 NMR, IR, UV-Visible spectroscopy, and single crystal X-ray diffraction. The compound crystallizes in the monoclinic space group P2(1)/c and crystals of (I) were found approximately 0.5:0.5 ratio to be twinned. The crystal structure is stabilized by N-H center dot center dot center dot N inter molecular hydrogen bonding. In addition to the molecular geometry and dimeric structure from X-ray experiment, the optimized molecular geometry for monomer and dimer, vibrational frequencies, atomic charges distribution, and total energies of the title compound in the ground state have been calculated using ab initio method. Density Functional Theory (B3LYP) and Hartree-Fock (HF) methods with basis sets 6-31G(d, p) and 3-21G were used in the calculations. Calculated frequencies are in good agreement with the corresponding experimental data. UV-Vis absorption spectra of the compound have been ascribed to their corresponding molecular structure and electrons orbital transitions.
Keywords: Hydrazine; Single crystal; ab initio calculations